Fiscal deficit and Nigeria economic growth (1990-2020) - Chinyere, Chigbo Nkeiruka (International research journal of management, IT and social sciences, 2021)
This paper focuses on fiscal deficit and Nigeria's economic growth. To achieve the objective of this study diagnostic check and unit root test using Phillips perron was employed to investigate time series data and to test the stationarity of the time series of the variables. Johansen co-integration analysis and Error Correction Model (ECM) are employed to test for a relationship between or among variables. The paper concludes that the driving variables of economic growth in Nigeria were Public external debt-PEXD, total federal collection revenue-TFCR, and interest rate-INTR. The public deficit financing was determined based on the study by the variables of Government expenditure (GOVE), real GDP, exchange rate-EXCR. The best model of ECM to determine the impact of fiscal deficit in Nigeria is the interaction with economic growth performance measures in Nigeria. The findings confirm that one standard deviation of shocks of fiscal deficit has a significant influence on economic growth, hence confirming the long-run relationship. The search recommended that Government should set its priority rights, be more committed to the budget implementation, and pay more attention to capital expenditure geared towards economic growth.